Effects of pre and post-veraison water deficit on Vermentino cluster microclimate and berry composition - Fernandes de Oliveira Ana; Mercenaro Luca; Azzena Mario; Nieddu Giovanni (BIO Web of Conferences, 2019)
The influence of light and thermal microclimate on berry quality of a Vermentino vineyard, managed with deficit irrigation strategies in north-western Sardinia, was analyzed. Two water deficit, pre- (ED) and post-veraison (LD), an irrigation (IC) and a non-irrigation (NC) control treatments were compared during berry development. Grapevine performances were evaluated by analyzing leaf gas exchange, source-sink balance, light and thermal microclimate effects on berry composition. Early and/or late deficit irrigation following a mild to moderate water stress threshold enabled high leaf physiological performances. Though with high stomatal conductance sensitivity to water deficit and anisohydric behavior, this variety exhibited high assimilation rate and quick recovery capacity after enduring moderate and severe water stress. All treatments achieved satisfactory sugar and acidic levels. Berry phenols were higher in LD due to lower canopy coverage and better light conditions compared to IC. Up to mid-ripening, cluster exposure to elevated temperatures negatively influenced phenolic accumulation, mostly in NC and to a lower extent in ED. In the last ripening weeks, total phenols was majorly influenced by light interception.